Meningkatkan Kinerja Pemasaran Ritel Tradisional melalui Innovation Capability dan Competitive Advantage - Anggraini, Dewi; Yasri, Yasri; Rasyid, Rosyeni (Universitas Batanghari Jambi, 2025)
This study aims to analyze the influence of innovation capability and competitive advantage on the marketing performance of grocery stores. The research method used is quantitative, by distributing questionnaires containing statements from each variable to 43 grocery store owners in Padang City. Data processing using multiple linear regression analysis. The results of this study reveal that innovation capability and competitive advantage have a positive and significant effect on the marketing performance of grocery stores in Padang City.